THE INFLUENCE OF 3D-PRINTING IN AIRCRAFT MAINTENANCE AND IN THE SUPPLY CHAIN - Borges, Diogo (2021)
This thesis aims to understand the impact three dimensional (3D) printing can have in aviation’s maintenance supply chain. Since optimizing every process related to fleet managing and safety compliance is the main goal of every aviation manager, 3D printing is a possible solution. Today’s methods and supply chain arrangement are outdated and should be changed in order to improve the product’s delivery. Every new technology has its upsides and downsides, as we will explore throughout this dissertation. The objective is to understand the benefits of 3D printed parts in the aviation’s maintenance workshop, and how it can affect the supply chain. This will be achieved through extensive research and by interviewing professionals from the aviation sector. Some of the results suggest that additive manufacturing will only represent an important part in maintenance in a distant future. Although it is possible to produce certified aircraft components nowadays, due to the fact aviation is a heavily regulated environment. Therefore, in the short term, 3D printing is only valuable for prototyping.